PEMBERDAYAAN MASYARAKAT PESISIR DONGGALA DALAM BUDIDAYA MANGROVE DI KELURAHAN KABONGA KECIL KECAMATAN BANAWA KABUPATEN DONGGALA - Suparman, Suparman; Tallesang, Mukhtar; Yohan, Yohan; Nurnaningsih, Nurnaningsih; Suirlan, Rita (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to empower coastal communities in Kabonga Kecil Village, Banawa District, Donggala Regency. A participatory approach (involving the community at every stage), educational efforts (providing training and outreach), and an economic-based approach (creating business opportunities from mangroves) are key to implementing this program. The method used is the Participatory Rural Appraisal (PRA) approach, combined with the concept of community-based development in coastal resource management. The results of this community service include the replanting of 500 mangrove seedlings in an abrasion-affected area of 1 hectare, with the involvement of approximately 25 people through mutual cooperation, consisting of community members, village heads, youth leaders, and the community service team, providing hope for the restoration of coastal ecosystems. In addition, an initial initiative was established in the form of a mangrove care group with 10 members, which synergizes with the Palu City Mangrovers community. In the economic aspect, it has been agreed to develop the area as a potential mangrove ecotourism destination, which is expected to become an alternative source of income for the local community.Kegiatan pengabdian ini bertujuan untuk melakukan pemberdayaan masyarakat pesisir di Kelurahan Kabonga Kecil Kecamatan Banawa Kabupaten Donggala. Pendekatan partisipatif (melibatkan masyarakat dalam setiap tahap), edukatif (memberikan pelatihan dan sosialisasi), serta berbasis ekonomi (menciptakan peluang usaha dari mangrove) menjadi kunci dalam pelaksanaan program ini. Metode yang digunakan melalui pendekatan Participatory Rural Appraisal (PRA) yang dipadukan dengan konsep community-based development dalam pengelolaan sumber daya pesisir. Capaian hasil pengabdian adalah menghasilkan penanaman kembali mangrove sebanyak 500 bibit di kawasan abrasi seluas 1 hektar dengan melibatkan sekitar 25 orang melalui gotong royong yang terdiri dari masyarakat, lurah, tokoh pemuda, dan tim pengabdian yang memberi harapan bagi pemulihan ekosistem pesisir. Selain itu, terbentuk inisiatif awal berupa 1 kelompok peduli mangrove yang beranggotakan 10 orang, yang bersinergi dengan komunitas Mangrovers Kota Palu. Dalam aspek ekonomi, telah disepakati pengembangan kawasan sebagai calon destinasi ekowisata mangrove, yang diharapkan menjadi sumber pendapatan alternatif bagi masyarakat lokal.